The Values Of Life In The Mysterious Bank of The Java Land Semiotic Studies - Nova, Emalia; Supratno, Haris; Suhartono, Suhartono (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2024)
The purpose of this study is to describe the life values and symbols written in the novel about the semiotic study of the unseen bank Java land story. This study uses a descriptive qualitative approach. The object and subject of this study is the novel with the title the unseen bank java land story novel published in 2019. The data in this study are the life values ??and symbols written in the unseen bank java land story in the novel by Bonaventura D. Genta, Mada Zidan, and Hari Kurniawan. The technique of data collection was carried out by reading in depth the novel and comprehending of the life values ??and symbols written in it. The technique of data analysis in this qualitative study is inductive which is an analysis based on the data obtained, firstly, classifying data that has been recorded in the data recording list based on the categories or classifications, secondly, the data that has been classified is further and deeper analyzed to be used as a basis for interpreting all the data and thirdly drawing a conclusion of the research results. The results of the study on the life values ?in the novel the unseen bank java land story in semiotic studies are (1) the religious values ??and moral values ??found in the novel unseen bank java land story.